Total pulmonary artery replacement with an Avalus‐Gelweave conduit in a patient with giant pulmonary artery aneurysm with pulmonary regurgitation. Issue 5 (16th March 2020) - Qian, Qi; Subbian, Senthil Kumar; Kofidis, Theo
Abstract: Background and aims: Pulmonary artery aneurysm is a rare disease. A 59‐year‐old Chinese female was diagnosed with idiopathic pulmonary aneurysm with pulmonary regurgitation. She had a past medical history of hemoptysis and systemic lupus erythematosus. Methods: She underwent a successful total pulmonary artery and valve replacement with an Avalus‐Gelweave conduit. Results: The postoperative echocardiogram showed a 7 mm Hg peak gradient across the prosthetic valve. The patient's postoperative recovery was uncomplicated. Conclusions: A bioprosthetic aortic valve can be used in a pulmonary position to achieve a good gradient and avoid long term anticoagulation therapy.